Оптимизация теплового и аэродинамического режимов работы туннельной печи для обжига керамического кирпича - Торчинский, А.И.; Ляшко, А.Ю. (Энерготехнологии и ресурсосбережение, 2016)
Тепловые и аэродинамические режимы обусловливают энергетически эффективный и качественный обжиг керамического кирпича в туннельных печах, работающих на природном газе. Рассмотрены основные принципы работы туннельной печи, распределение аэродинамических потоков по длине печи и влияние аэродинамического режима на качество обжига. Выполнен анализ кривой статического давления туннельной печи. Обоснованы оптимальные аэродинамические и тепловые параметры обжига керамического кирпича. Приведена схема движения газовоздушных потоков и соответствующий ей график распределения статического давления по длине рабочего канала туннельной печи. Рассмотрен способ управления объемами теплоносителя. Теплові та аеродинамічні режими зумовлюють енергетично ефективний та якісний випал керамічної цегли у тунельних печах, що працюють на природному газі. Розглянуто основні принципи роботи тунельної печі, розподіл аеродинамічних потоків по довжині печі та вплив аеродинамічного режиму на якість випалу. Виконано аналіз кривої статичного тиску тунельної печі. Обгрунтовано оптимальні аеродинамічні та теплові параметри випалу керамічної цегли. Наведено схему руху газоповітряних потоків та відповідний їй графік розподілу статичного тиску за довжиною робочого каналу тунельної печі. Розглянуто спосіб управління об’ємами теплоносія. Based on the research of operating tunnel furnaces and their analysis there were identified bottlenecks in the calcination process of ceramic bricks in tunnel kilns and proposed optimal thermal and aerodynamic modes, which determine energy-efficient and high-quality calcination of a ceramic brick in tunnel kilns, operating on natural gas. The basic principles of operation of a tunnel kiln, the distribution of the aerodynamic flow along the length of the furnace and the influence of the aerodynamic regime on the quality of calcination have been studied. The detailed analysis of the static pressure curve of the tunnel kiln was carried out. The optimal aerodynamic and thermal characteristics of ceramic bricks calcination. The concept of an availability of the necessary equipment and its optimum location is considered. The scheme of gas-air flows motion and the corresponding graph of the distribution of static pressure along the length of the working channel of a tunnel kiln are presented. The method of controlling the volume of heat carrier is considered.